CHARACTERISTICS OF PATIENTS DENGUE HEMORRHAGIC FEVER THE HOSPITALIZED AT SANTA ELISABETH MEDAN HOSPITAL IN 2016 - noni efriana sinurat; Fazidah Siregar; Sri Novita Lubis (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2017)
ABSTRACT Dengue Hemorrhagic Fever is a health problem that is widespread throughout the world, especially in the tropics area. The disease can affect all people and can lead to death, especially in children.It can also extraordinary events or outbreaks. In 2014 Incidence rate 39.80 per 100,000 population. In 2015 IR 50.75 per 100,000 population and CFR 0.83%. To know the characteristic of DHF patients who were hospitalized at Santa Elisabeth Hospital Medan, descriptive research with case series design was conducted. The population is all data of DHF patient in 2016, 884 data and 275 samples of DHF data using Simple Random Sampling technique. The highest proportion of sosiodemographic 5-14 years old (34.9%), male (53.1%), Batak (90.2%), Protestant (69.1%), 55,6%), in Medan (55,6%), platelet count <150.000/mm3 (81,1%), home platelet <150.000/mm3 (57,8%), increment of hematocrit at <20% 79,6%), increase of hematocrit at home <20% (93,5%), level I (62,2%), treatment with fluid (95,6%), own cost (54,5%), (94.9%), average length of stay 5.19 days, age based on highest severity, level I <15 years (56.7%), level II 15-45 years (53.9% ), level III <15 years (47,4%) and level IV <15 years (88,9%),dead (100%) has a platelet count <150.000/mm3, the hematocrit increase is based on the highest return home state is <20% ie heal/repair 93,9%, PAPS 91,7%, dead 50%. Patients PAPS (100%) use own cost, there was no significant difference in mean duration of treatment (day) based on severity (p = 0,119). It is expected that the people in Medan can work together to prevent the spread of DHF and to the hospital to complete the recordingeducation on the status card. Keywords: Dengue haemorrhagic fever, patient characteristics, Santa Elisabeth hospital.